Comment on "Conductance scaling in Kondo-correlated quantum dots: Role of level asymmetry and charging energy" - Aligia, Armando Angel (2014)
In a recent work [Merker, Kirchner, Muñoz, and Costi, Phys. Rev. B 87, 165132 (2013)], the authors compared the results of numerical renormalization group (NRG) and a perturbative approach for the dependence on temperature T and magnetic field B of the conductance through a quantum dot described by the impurity Anderson model, for small T and B. We show that the equation used to extract the dependence on B from NRG results is incorrect out of the particle-hole symmetric case. As a consequence, in the Kondo regime, the correct NRG results have a weaker dependence on B and the disagreement between both approaches increases.